Peradaban Islam di Afrika Utara Masa Dinasti Murabithun, Muwahidun dan Fatimiyah - Hasbiyallah Romli (IAIN Syekh Nurjati Cirebon, 2022)
In Arabic terminology, the regions that are part of the North African region are: the lower Nile basin called Egypt, Libya, Cyenacia, Tripolitania and Tunisia, all of which the Arabs call Africa; besides that the Algeria and Morocco regions, by the Arabs known as al-Maghribi. The development of Islam in North Africa itself has started since the time of the caliph Umar bin Khattab (634-644 AD), who sent Amru bin Ash to conquer and control Egypt and systematically continued the development of the North African region by the dynasties that ruled after him. North Africa is an important area that has become a springboard for the spread of Islam to Europe. Therefore, Islam which has developed rapidly in the Arabian peninsula and at the same time as a political force, considers it important to control the North African region as a bridge towards the spread of Islam in the European region.